Beyond Fascism: A Research Agenda on The New Far Right in Latin America - Alenda, Stéphanie; Escoffier, Simón (Revista de Historia Social y de las Mentalidades, 2024)
New particularities of the far-right in Latin America have allowed it to gain power over the last couple of decades. While the ideas of fascism and Nazism adequately reflected the development of authoritarian, xenophobic, and populist ideological forces during the first half of the 20th century, today, they are obsolete for referring to the tactics and impacts of this new far-right. Although conceptual frameworks on the issue invited to (re)classify the new ultra-right tendencies, the article proposes a relational perspective that identifies dynamics, evolutions, and positions of different expressions of the far right. After a conceptual and historical overview of the relationships between the new far right and fascism, we propose two avenues for future research. First, we explain that the growth of the new far-right depends mainly on the evolution of relationships and disputes between the institutional expressions of the right in their most radical and moderate versions. Second, we show that exploring the development of far-right civil society concerning institutional politics is essential for understanding its recent expansion.
Keywords: Far-right; Fascism; Latin America; Right-wing; Civil Society